2020
DOI: 10.14744/turkjfas.2019.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preharvest GA3, CaCl2 and modified atmosphere packaging treatments on specific phenolic compounds of sweet cherry

Abstract: The fruit of sweet cherry are more sensitive against external factors than many fruit species so post harvest quality loss on sweet cherry is quite higher. For this reason, it is very significant to reduce the postharvest losses and to extend the storage period in sweet cherry, and this is one of the main objectives for producers and consumers. The aim of the study was to determine the effects of GA3, CaCl2 and modified atmosphere packaging (MAP) applications on individual phenolics compounds in postharvest st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Homogeneously colored sweet cherry fruit is more demanding in the market and can be marketed at higher prices (Aglar et al, 2019;Ozturk et al, 2019). Fruit color varies depending on genetic factors in all species and cultivars.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Homogeneously colored sweet cherry fruit is more demanding in the market and can be marketed at higher prices (Aglar et al, 2019;Ozturk et al, 2019). Fruit color varies depending on genetic factors in all species and cultivars.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In this regard, it has been reported that calcium‐treated fruits had a strong cell wall structure at postharvest, resulting in reduction in fruit decay and extending fruit shelf‐life (Figueroa et al., 2012). Furthermore, recent studies demonstrated that calcium minimized damages inflicted to cell membranes and delayed senescence processes because of hindering ethylene biosynthesis, thereby increasing fruit maintenance after harvesting (Kou et al., 2014; Ozturk et al., 2019; Serrano et al., 2004). The results of this research also substantiated the role of calcium in augmenting CAT and POD activity and decreasing PPO activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was then held for 8 seconds, and reading was done at the end of the 15 th second. Results presented as g kg −1 (Ozturk et al, 2019).…”
Section: Soluble Solids Contnt Titratable Acidity and Vitamin Cmentioning
confidence: 99%